2020
DOI: 10.3324/haematol.2019.246058
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-driven lipolysis and bone marrow niche remodeling support leukemia expansion

Abstract: Publisher's Disclaimer. E-publishing ahead of print is increasingly important for the rapid dissemination of science. Haematologica is, therefore, E-publishing PDF files of an early version of manuscripts that have completed a regular peer review and have been accepted for publication. E-publishing of this PDF file has been approved by the authors. After having E-published Ahead of Print, manuscripts will then undergo technical and English editing, typesetting, proof correction and be presented for the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In knockin syngeneic AML/acute lymphoblastic leukemia (ALL) mouse models, tumor-derived EVs increased the expression of adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) enzymes in adipocytes, resulting in increased lipolysis, which supported leukemia cell expansion ( 53 ). Similarly, miR-92a-3p–containing EVs derived from a CML cell line (K562) attenuated adipogenesis of an adipose-derived MSC cell line (ADSCs) by inhibiting CCAAT/enhancer binding protein-α (C/EBPα).…”
Section: Functions Of Evs In Hematologic Malignanciesmentioning
confidence: 99%
“…In knockin syngeneic AML/acute lymphoblastic leukemia (ALL) mouse models, tumor-derived EVs increased the expression of adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) enzymes in adipocytes, resulting in increased lipolysis, which supported leukemia cell expansion ( 53 ). Similarly, miR-92a-3p–containing EVs derived from a CML cell line (K562) attenuated adipogenesis of an adipose-derived MSC cell line (ADSCs) by inhibiting CCAAT/enhancer binding protein-α (C/EBPα).…”
Section: Functions Of Evs In Hematologic Malignanciesmentioning
confidence: 99%
“…Leukemic cells and leukemic stem cells reside in the bone marrow and lymphatic niches that resemble a glucose-deprived and hypoxic TME, which is comparable to the conditions seen in solid tumors. Two recent studies demonstrated that acute myeloid leukemia (AML) cells remodel their direct environment by secretion of exosomes that, in turn, promote MSC differentiation towards adipocytes and lipolysis in already differentiated adipocytes [ 56 , 57 ]. Moreover, adipose tissue is beneficial for AML blasts and leukemic stem cells (LSCs) by increasing FAO and CD36/FABP4 expression, resulting in the prevention of serum starvation-induced apoptosis and protection from chemotherapy [ 58 , 59 ].…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%
“…In the context of active leukemia, the bone marrow niche undergoes a number of physical and functional changes. Compared to healthy marrow, leukemic marrow commonly exhibits hypercellularity, enhanced extracellular matrix deposition, vascular adhesion protein expression, and vascular permeability [13][14][15][16][17] . However, little is known regarding the circulation properties of leukemia cells or the factors that regulate circulation.…”
Section: Introductionmentioning
confidence: 99%